2021
DOI: 10.1126/sciimmunol.abg5021
|View full text |Cite
|
Sign up to set email alerts
|

Integrated longitudinal immunophenotypic, transcriptional, and repertoire analyses delineate immune responses in patients with COVID-19

Abstract: To understand how a protective immune response against SARS-CoV-2 develops over time, we integrated phenotypic, transcriptional and repertoire analyses on PBMCs from mild and severe COVID-19 patients during and after infection, and compared them to healthy donors (HD). A type I IFN-response signature marked all the immune populations from severe patients during the infection. Humoral immunity was dominated by IgG production primarily against the RBD and N proteins, with neutralizing antibody titers increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 93 publications
7
100
0
Order By: Relevance
“…HEK 293TN hACE2 cells were derived from HEK 293TN after transduction with a lentiviral vector coding for human ACE2 gene and Hygromycin resistance as previously described. 13 …”
Section: Methodsmentioning
confidence: 99%
“…HEK 293TN hACE2 cells were derived from HEK 293TN after transduction with a lentiviral vector coding for human ACE2 gene and Hygromycin resistance as previously described. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a higher proportion of SARS-CoV-2 specific CD8 + T cells were detected in mild cases, and these CD8 + T cells have extensive and strong memory after the recovery period of COVID-19 [ 14 ]. On the contrary, a significant reduction in effector memory CD4 + T cells, which were less expanded and skewed toward central memory T cells and TH2-like phenotypes, was detected in COVID-19 patients with severe disease, whereas terminally differentiated CD8 + GZMK + effector cells were clonally expanded both during and after the infection [ 15 ]. The CD4 + T memory response was detected in all recovered patients from COVID-19, and 70% of patients had established CD8 + T memory response to SARS-CoV-2, lasting for more than 2 months [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, individual immune responses potentially orchestrate the pathology and play important roles in determining different clinical courses of SARS-CoV-2 infection. A recent study showed an extensive and durable remodeling of immune cells during and after SARS-CoV-2 infection [11]. However, the immune mechanisms that are associated with asymptomatic infection are still largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Different clusters had different transcriptional characteristics and functional phenotypes. The proportion of different subpopulations was closely related with severity of COVID-19 [11]. In the future, to accurately reflect the characteristics of immune phenotype of asymptomatic and symptomatic cases, it is necessary to analyze NK and monocyte clusters.…”
Section: Discussionmentioning
confidence: 99%